A new-to-nature photosynthesis system enhances utilization of one-carbon substrates in Escherichia coli - Tian Tong; Xiulai Chen; Kexin Tang; Wanrong Ma; Cong Gao; Wei Song; Jing Wu; Xiaoling Wang; Gao-Qiang Liu; Liming Liu (Nature Communications)
Abstract Photosynthesis harvests solar energy to convert CO2 into chemicals, offering a potential solution to reduce atmospheric CO2. However, integrating photosynthesis into non-photosynthetic microbes to utilize one-carbon substrates is challenging. Here, a photosynthesis system is reconstructed in E. coli, by integrating light and dark reaction to synthesize bioproducts from one-carbon substrates. A light reaction is reconstructed using the photosystem of photosynthetic bacteria, increasing ATP and NADH contents by 337.9% and 383.7%, respectively. A dark reaction is constructed by designing CO2 fixation pathway to synthesize pyruvate. By assembling the light and dark reaction, a photosynthesis system is established and further programmed by installing an energy adapter, enabling the production of acetone, malate, and α-ketoglutarate, with a negative carbon footprint of −0.84 ~ −0.23 kgCO2e/kg product. Furthermore, light-driven one-carbon trophic growth of E. coli is achieved with a doubling time of 19.86 h. This photosynthesis system provides a green and sustainable approach to enhance one-carbon substrates utilization in the future.